2019
DOI: 10.1007/s40843-019-1184-y
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced directional domain sliding motion in peptide hydrogels promotes ectodermal differentiation of embryonic stem cells

Abstract: Mechanical cues present in the stem cell niche resulting from intracellular processes or external force sources significantly affect the basic functions of stem cells such as self-renewal and differentiation. Creation of artificial cellular matrices exhibiting intrinsic mechanical cues generated by mechanical movements remains scarce. Herein, we reported on mechanically dynamic hydrogel matrices undergoing photo-induced directional domain sliding movement and their role in regulating embryonic stem cell (ESC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…The mechanistic studies revealed that the enhanced cellular proliferation is attributed to the conventional Hippo mechanotransduction pathway involving translocation of unphosphorylated YAP protein into cell nuclear, which subsequently activated the downstream proliferation‐related genes. Simultaneously, we also found the photo‐regulated molecular movement in mechanical hydrogels affected the differentiation of embryonic stem cells [133] . This kind mechanically dynamic hydrogels are the first examples of artificial extracellular matrices able to actively stimulate cells by intrinsic mechanical cue, thus providing a unique strategy for regulating cell fate through materials engineering.…”
Section: Biomedical Applications Of In Situ Peptide Assembliesmentioning
confidence: 62%
See 1 more Smart Citation
“…The mechanistic studies revealed that the enhanced cellular proliferation is attributed to the conventional Hippo mechanotransduction pathway involving translocation of unphosphorylated YAP protein into cell nuclear, which subsequently activated the downstream proliferation‐related genes. Simultaneously, we also found the photo‐regulated molecular movement in mechanical hydrogels affected the differentiation of embryonic stem cells [133] . This kind mechanically dynamic hydrogels are the first examples of artificial extracellular matrices able to actively stimulate cells by intrinsic mechanical cue, thus providing a unique strategy for regulating cell fate through materials engineering.…”
Section: Biomedical Applications Of In Situ Peptide Assembliesmentioning
confidence: 62%
“…Simultaneously, we also found the photo-regulated molecular movement in mechanical hydrogels affected the differentiation of embryonic stem cells. [133] This kind mechanically dynamic hydrogels are the first examples of artificial extracellular matrices able to actively stimulate cells by intrinsic mechanical cue, thus providing a unique strategy for regulating cell fate through materials engineering.…”
Section: Cell Culture and Tissue Regenerationmentioning
confidence: 99%